Depression and Anxiety Disorders among Patients with Psoriasis: A Hospital-Based Case-Control Study - Masoud Golpour; Seyed Hamzeh Hosseini; Mohammad Khademloo; Maryam Ghasemi; Aghdas Ebadi; Fatemeh Koohkan; Soheila Shahmohammadi (Dermatology Research and Practice)
Background. Psoriasis is a common, genetically determined inflammatory and proliferative disease of the skin. Psychological stress can exacerbate the disease. This study sought to investigate the depression and anxiety disorders among patients with psoriasis and control group. Method. In this hospital-based case-control study, One hundred patients with psoriasis (case) referred to the dermatology department and 100 patients with otolaryngology problems and dermatological healthy volunteers (control) who referred to the Otolaryngology Department of Bouali Sina Hospital in Sari, Iran, in 2007 were studied. Demographic characteristics were recorded. Beck Depression Inventory and Spielberger State-Trait Anxiety Scale I-II were administered to the patients in both groups. Data were analyzed using SPSS statistical software and descriptive statistical tests. Results. From One-hundred patients in each group, 44 (45%) were men. Depression score was 67% and 12% in psoriatic patients and control, respectively. The Beck depression scores of patients with psoriasis were significantly higher than scores of the control group (𝑃<0.05). Based on Spielberger State-Trait Anxiety Scale, anxiety was found in 45% of patients in case group and 18% of controls. Conclusion. The results revealed that psoriatic patients reported significantly higher degrees of depression and anxiety than controls. In addition, psoriatic women were more depressed than psoriatic men.